Напружено-деформований стан циліндричних оболонок з еліптичним поперечним перерізом зі скісними зрізами - Григоренко, Я.М.; Григоренко, О.Я.; Крюков, М.М.; Яремченко, С.М. (Доповіді НАН України, 2020)
Дано розв'язок задачі про згин циліндричних оболонок з еліптичним поперечним перерізом зі скісними зрізами. За вихідні вибрано рівняння теорії оболонок на основі гіпотези прямої лінії. Підхід до розв'язання базується на параметризації поверхні оболонки, зведенні двовимірної крайової задачі до одновимірної методом сплайн-колокації та розв'язанні останньої стійким чисельним методом дискретної ортогоналізації. Проаналізовано вплив змінних геометричних параметрів на поля переміщень оболонок кругового і еліптичного поперечного перерізу зі скісними зрізами. The solution to the problem on the bending of cylindrical shells with an elliptic cross-section with beveled
cuts is given. The relations of the theory of shells based on the straight line hypothesis is used. Systems of partial
differential equations are obtained from the equilibrium equations of shell theory for determining displace ments
and total angles of rotation of a non-circular cylindrical shell. The initial relations are written for an orthogonal
coordinate system, the coordinate lines of which are the generatrix and directrix of the cylinder. A new
non-orthogonal coordinate system is chosen and associated with the original one. The non-rectangular region
of the old system for a non-circular shell with beveled cuts is transformed into a rectangular one in the new
coordinates by the substitution of the coordinates. This allowed us to use the spline-collocation method to
reduce two-dimensional boundary problem, which describes the stress-strain state of the shell, to a one-dimensional one. The one-dimensional boundary-value problem is solved by a stable numerical method of discrete orthogonalization. Using the described approach, problems of the stress-strain state of closed shells with an elliptic cross-section under the action of a uniformly distributed internal pressure with clamped beveled cuts are solved. To assess the reliability of the approach using the described methodology, problems for non-circular shells without beveled cuts, as well as for circular shells with beveled cuts, which are special cases, are solved. The displacements of the mid-surface of the shells are compared depending on the cut angles for circular and elliptic cross-section shells. Дано решение задачи об изгибе цилиндрических оболочек с эллиптическим поперечным сечением со скошенными срезами. В качестве исходных выбраны уравнения теории оболочек на основе гипотезы прямой
линии. Подход к решению основан на параметризации поверхности оболочки, приведении двумерной
краевой задачи к одномерной методом сплайн-коллокации и решении последней устойчивым численным
методом дискретной ортогонализации. Проанализировано влияние переменных геометрических параметров на поля перемещений оболочек кругового и эллиптического сечения с косыми срезами.